Contre le courant - Lenin, Vladimir Iljitsj; Zinovjev, Grigori; Serge, Victor; Parijanine, Maurice (Paris: Maspero, 1970)
"N. Lénine, G. Zinoviev ; traduit par V. Serge et Parijanine Fonds PerroneBibliotheek François Vercammen"